Studi komparatif engagement rate konten kecantikan berdasarkan tier influencer TikTok: nano, micro, macro, mega - Revalina Renata; Ratih Amelia (Universitas Widya Mataram, 2026)
TikTok has become one of the primary platforms for influencer marketing strategies among beauty brands in Indonesia. However, the assumption that mega influencers always generate the highest engagement has not been widely tested empirically. This study compares the engagement rate (ER) of beauty content across four influencer tiers, namely nano, micro, macro, and mega influencers on Indonesian TikTok. Data were collected through non-participant observation of 120 videos from 12 accounts using purposive sampling. Data analysis was conducted using the Kruskal-Wallis test and post hoc Mann-Whitney test with Bonferroni correction. The results revealed a significant difference in ER among the four influencer tiers (H = 17.311; p = 0.001; ε² = 0.145). Macro influencers had the highest mean ER (11.634%) and differed significantly from all other tiers. In contrast, mega influencers were not consistently superior, while nano influencers were not found to have the lowest ER. Mega influencers also showed the most consistent performance, indicated by the lowest coefficient of variation (48.3%). Theoretically, these findings indicate that the relationship between follower count and engagement is not linear within TikTok's algorithm-driven ecosystem. This study provides empirical insights for beauty brands in selecting influencer tiers according to campaign objectives on TikTok.